2022
DOI: 10.1186/s12913-022-08784-8
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of health and the prediction of missed breast imaging appointments

Abstract: Background Predictive models utilizing social determinants of health (SDH), demographic data, and local weather data were trained to predict missed imaging appointments (MIA) among breast imaging patients at the Boston Medical Center (BMC). Patients were characterized by many different variables, including social needs, demographics, imaging utilization, appointment features, and weather conditions on the date of the appointment. Methods This HIPAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Research outside of ophthalmology has investigated the burden of these factors on appointment attendance, with one study on breast imaging revealing housing insecurity, difficulty paying utility bills, and low income as predictors of missed clinic appointments. 21 In ophthalmology, a study revealed that neighborhood-level social vulnerability increased appointment nonattendance. 22 These findings highlight the importance of understanding the conditions and communities where patients reside and how these factors contribute to their overall health status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research outside of ophthalmology has investigated the burden of these factors on appointment attendance, with one study on breast imaging revealing housing insecurity, difficulty paying utility bills, and low income as predictors of missed clinic appointments. 21 In ophthalmology, a study revealed that neighborhood-level social vulnerability increased appointment nonattendance. 22 These findings highlight the importance of understanding the conditions and communities where patients reside and how these factors contribute to their overall health status.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 55% of patients reported facing at least one social risk factor. Research outside of ophthalmology has investigated the burden of these factors on appointment attendance, with one study on breast imaging revealing housing insecurity, difficulty paying utility bills, and low income as predictors of missed clinic appointments 21 . In ophthalmology, a study revealed that neighborhood-level social vulnerability increased appointment nonattendance 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In one of the most robust studies to date, Sotudian et al used a dataset of 9,970 patients and 36,606 to develop linear and non-linear models to identify predictive variables for missed breast imaging appointments ( 15 ). Among the 57 potentially impactful variables analyzed, the investigators found that those related to social determinants of health including housing insecurity, difficulty paying utility bills, and family caretaking were among the strongest in predicting for “no shows.”…”
Section: Discussionmentioning
confidence: 99%
“…Conventional Machine Learning (ML) algorithms are generally designed to minimize regression or classification errors [12,13,16,32,42]. Many real-world applications, on the other hand, deemphasize prediction accuracy and prioritize the correct ordering among all the instances [33,34].…”
Section: Introductionmentioning
confidence: 99%